Lactic acid production from renewable resources - Coelho, Luciana Fontes [UNESP]; Bernardo, Marcela Piassi [UNESP]; de Oliveira, Paola Monteiro [UNESP]; de Lima, Cristian Jacques Bolner [UNESP]; Contiero, Jonas [UNESP] (My University, 2012)
Lactic acid has been used in pharmaceutical, cosmetic, chemical and food industries. It can be used as a raw material in biodegradable plastics, such as polylactic acid (PLA) as well as to improve the physical properties in the production of garbage bags, agricultural plastic sheeting, and food packaging. It can also be used in sutures and surgical implants due to its biocompatible and bioabsorbable characteristics. Lactic acid is industrially produced either through chemical synthesis or microbial fermentation.The advantage of the biological method is that an optically pure lactic acid can be obtained by choosing a strain of lactic acid bacteria, whereas chemical synthesis always results in a racemic mixture of lactic acid. The optical purity of lactic acid is very important to the physical properties of PLA and obtaining a more stable crystalline polymer than that achieved with a racemic lactic acid. Therefore, raw materials for the industrial production of lactic acid need to have characteristics such as low cost, low levels of contaminants, rapid fermentation, and year-round availability. The cost of raw materials represents 68% of the total cost of lactic acid production. A number of industrial byproducts or wastes have been evaluated as substrates for lactic acid production with the aim of decreasing the cost of the process, such as sugarcane, molasses, cassava wastewater, and whey as carbon sources and corn steep liquor (CSL) and yeast autolysate as nitrogen sources. In this chapter, it will be discussed the fermentation technology to lactic acid production that has been used and exploited by using the cheaply available source materials. © 2012 Nova Science Publishers, Inc. All rights reserved.
Keywords: Biodegradable polymer; Fermentation; Lactic acid; Lactic acid bacteria; Poly(lactic acid)